Research in the Dark: Explorations into the Societal Effects of Light and Darkness. Issue 2 (1st June 2019) - Schulte-Römer, Nona
Abstract : Edensor, Tim. 2017. From Light to Dark: Daylight, Illumination, and Gloom. Minneapolis: University of Minnesota Press. Bille, Mikkel. 2019. Homely Atmospheres and Lighting Technologies in Denmark: Living with Light. New York: Bloomsbury Academic.